(untitled) (Revista de História Regional, 2021)
The article offers some descriptions of practices and reflections that are important for the knowledge of the modernization process of the water distribution system in The City of Goiás, during the first half of the 20th century. The experience of protagonists of the city in the water channeling procedures indicated the need for domestic transportation, transportation by new routes, discipline for men,redefining norms, and obligations. In this context, the strategies adopted by the city government were problematized, to face the process of appropriation and control of water, to build underground supply networks, linking fountains and reservoirs to private spaces for domestic use. From this central problem, it is about investigating the birth of a new way of using water associated with strategies that involve management procedures associated with programs led by municipal powers. Reading and interpreting documents are available at the Frei Simão Dorvi Historical Archive, in the City of Goiás, which guided the development of this research.